Can AI Standardize Medical Image Reporting? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Medical imaging is a cornerstone of modern diagnostics, providing critical insights into a patient's health. However, the interpretation and reporting of med...
Keywords: AI in Medical Imaging and Diagnostics; Standardize; Medical; Image; Artificial Intelligence; Machine Learning; Healthcare